PENINGKATAN KEMAMPUAN MENGENAL KONSEP BILANGAN ANAK USIA 5-6 TAHUN MENGGUNAKAN MEDIA POP-UP BOOK DI TK PERTIWI 1 KOTA PADANG - Tesya Cahyani Kusuma; nurama wahyuni (FKIP Universitas sriwijaya, 2018)
Improved Ability to Know the Concept of 5-6 Years Ages Using Pop Up Book Media in TK Pertiwi 1 Padang. The aim of this research is to know the improvement of the ability to recognize the concept of the number of children aged 5-6 years using Pop-Up Book media. This study was conducted with 16 children. This study consists of two cycles, each cycle consisting of 5 meetings. Data analysis using simple percentage formula according to Purwanto. The result of the research shows that in the pre-cycle stage, the data of the concept ability level is 56.56%. Then it increased to 63.16% at the end of cycle I and increased to 79.70% at the end of cycle II.